The Patronization of Pluvial Flood Risk and Adaptation Among Tenant-Owned Housing Associations in Sweden - Mattias Hjerpe; Erik Glaas; Sofie Storbjörk (Buildings)
Pluvial floods are increasingly affecting urban areas worldwide. Despite growing media attention and clear owner responsibility for reducing climate-related risk for buildings in Swedish national adaptation policy, adaptation action remains slow. Understanding how different property owner categories view and act on flood risks is key for developing better incentive structures and support for accelerating adaptation action. While tenant-owned housing is a common form of housing tenure in Sweden, studies are lacking. This study enhances understanding of pluvial flood risk and adaptation views and actions by tenant-owned housing associations in two Swedish cities. It is based on assessments of 69 apartment buildings within eleven tenant-owned associations and semi-structured interviews with their eleven chairpersons. The study indicates that tenant-owned associations grossly underestimate their flood risks and responsibilities for climate adaptation, even though many buildings studied are at significant risk, and most associations have been impacted by floods, some severely and recurrently. The patronization of flood risk and responsibility for adaptation is attributed to several factors: underestimating risks and consequences, devaluing the benefit of one’s own adaptation actions, lacking knowledge about climate adaptation measures for buildings, and (overly) generous insurance terms. The findings confirm low adaptation action among housing associations, even those with recurring floods, which is concerning given the strong reliance on property-owner adaptation in national adaptation policy.